2020
DOI: 10.1007/s00415-020-10150-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary or secondary chronic functional dizziness: does it make a difference? A DizzyReg study in 356 patients

Abstract: In 2017, the term "persistent postural-perceptual dizziness" (PPPD) was coined by the Bárány Society, which provided explicit criteria for diagnosis of functional vertigo and dizziness disorders. PPPD can originate secondarily after an organic disorder (s-PPPD) or primarily on its own, in the absence of somatic triggers (p-PPPD). The aim of this database-driven study in 356 patients from a tertiary vertigo center was to describe typical demographic and clinical features in p-PPPD and s-PPPD patients. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 49 publications
(54 reference statements)
8
40
1
6
Order By: Relevance
“…Furthermore, symptom provocation by position changes in bed may point to BPPV as another vestibular disorder triggering secondary functional dizziness. This findings agree with previous literature ( 8 ). Interestingly, patients with primary functional dizziness had higher fear and depression scales, which may indicate a more intense psychological symptom burden.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, symptom provocation by position changes in bed may point to BPPV as another vestibular disorder triggering secondary functional dizziness. This findings agree with previous literature ( 8 ). Interestingly, patients with primary functional dizziness had higher fear and depression scales, which may indicate a more intense psychological symptom burden.…”
Section: Discussionsupporting
confidence: 94%
“…In the second classification task, two groups of patients with functional dizziness were compared, who were presumably very similar in their symptomatic presentation, but differed in the evolution of their symptoms: patients with primary functional dizziness, where chronic psychological stress or anxiety is the driving force, and patients with secondary functional dizziness, which develops after a preceding somatic vestibular disorders (e.g., BPPV) due to altered balance perception and strategies of postural control ( 8 ). Accordingly, top 10 features for classification included vestibular function tests (such as vHIT gain left/right and caloric response normal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Funktionelle Schwindelsyndrome können entweder primär ohne organisch-vestibuläre Störung oder sekundär bei abgelaufenen oder aktiven Vestibulopathien (z.B. BPPV, Morbus Menière, vestibuläre Migräne) auftreten [73]. In der Bárány-Klassifikation wird als Synonym für den funktionellen Schwindel der persistierende subjektive Schwankschwindel (persistent postural-perceptual dizziness, PPPD) verwendet [74].…”
Section: Funktionelle Schwindelsyndromeunclassified
“…PPPD affects men and women at all ages. Several clinical epidemiological studies of PPPD have been published worldwide and showed a female predominance [5][6][7]. It is characterized by persisting subjective dizziness, unsteadiness or non-rotational vertigo for at least three months and may be exacerbated by upright posture including the patient's own movement as well as motion of complex visual stimuli [4].…”
Section: Introductionmentioning
confidence: 99%